2019
DOI: 10.1155/2019/2647068
|View full text |Cite
|
Sign up to set email alerts
|

NRF1 and NRF2 mRNA and Protein Expression Decrease Early during Melanoma Carcinogenesis: An Insight into Survival and MicroRNAs

Abstract: The prognostic significance of the major redox regulator nuclear factor erythroid-2-related factor (NRF2) is recognized in many cancers, but the role of NRF1 is not generally well understood in cancer. Our aim was to investigate these redox transcription factors in conjunction with redox-related microRNAs in naevi and melanoma. We characterized the immunohistochemical expression of NRF1 and NRF2 in 99 naevi, 88 primary skin melanomas, and 67 lymph node metastases. In addition, NRF1 and NRF2 mRNA and miR-23B, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…The specific biological function of Klf5 is considered as transcription factor to regulate cell proliferation, apoptosis, migration, and differentiation [30,31]. The other study also indicated that Nrf1 was involved in the melanoma carcinogenesis [32]. Hence, our results…”
Section: Discussionsupporting
confidence: 64%
“…The specific biological function of Klf5 is considered as transcription factor to regulate cell proliferation, apoptosis, migration, and differentiation [30,31]. The other study also indicated that Nrf1 was involved in the melanoma carcinogenesis [32]. Hence, our results…”
Section: Discussionsupporting
confidence: 64%
“…The speci c biological function of Klf5 is considered as transcription factor to regulate cell proliferation, apoptosis, migration, and differentiation [33,34]. The other study also indicated that Nrf1 was involved in the melanoma carcinogenesis [35]. Hence, our results provided a new research direction for the research of Klf5 and Nrf1.…”
Section: Discussionsupporting
confidence: 53%
“…Among these miRNAs, miR-144-3p played an important role in the regulation of NRF2. Targeting NRF2 by miR-144-3p inhibited tumor progression in melanoma and acute myeloid leukemia 86 , and increased the sensitivity of lung cancer cells to cisplatin 87 , indicating the role of miR‑144‑3p in oxidative homeostasis. Other miRNAs that targeted NRF2 include miR-144 , miR-153 , miR-200c , and miR-212-3p , although their effects have not been explored 82 , 88 – 90 .…”
Section: Introductionmentioning
confidence: 99%